2013
DOI: 10.17795/jhealthscope-10736
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Aflatoxin in the Imported Rice in Zahedan, South-East of Iran, 2011

Abstract: Background: Rice is common foodstuffs in Iran. Aflatoxin contamination of rice can be hazardous human health and causes economic problems. Objectives: Determination of Aflatoxin levels was investigated on the imported rice which is consumed as the main food in this area. Materials and Methods: Two hundred samples of imported rice consisting; yellow (100) and white (100) rice were selected randomly. These samples were assessed for Aspergillus infection and the Aflatoxins B, G was detected by high performance li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The results similarly revealed that contaminations in white rice could be more than those yellow ones. Moreover, no imported rice had contamination caused by AFTs higher than standard levels, and the amount of AFB1 was below the internationally acceptable limits for human use, which were consistent with the findings by Mazaheri in which the mean of AFB1 was reported lower than Iranian maximum tolerated limit (MTL) (35). Furthermore, Feizy et al (30) reported that 68.9% of the rice samples (n = 261) had AFB1 at levels greater than 0.2 ng.g -1 .…”
Section: Aflatoxinssupporting
confidence: 88%
See 2 more Smart Citations
“…The results similarly revealed that contaminations in white rice could be more than those yellow ones. Moreover, no imported rice had contamination caused by AFTs higher than standard levels, and the amount of AFB1 was below the internationally acceptable limits for human use, which were consistent with the findings by Mazaheri in which the mean of AFB1 was reported lower than Iranian maximum tolerated limit (MTL) (35). Furthermore, Feizy et al (30) reported that 68.9% of the rice samples (n = 261) had AFB1 at levels greater than 0.2 ng.g -1 .…”
Section: Aflatoxinssupporting
confidence: 88%
“…Besides, the amount of AFB1 in 8.3% of the sam-ples was higher than the maximum annual concentration (MAC) in foodstuff in Iran. AFB1 was also reported as the highest amount of contamination in the study by Karajibani et al (35), but AFG1 and G2 were not detected in the samples. The results similarly revealed that contaminations in white rice could be more than those yellow ones.…”
Section: Aflatoxinsmentioning
confidence: 74%
See 1 more Smart Citation
“…Karajibani et al (2013) reported that AFB1 and AFB2 in 33% and 47% of yellow and white rice samples were contaminated with 0.34 and 0.58 ppb, respectively. It was also detected 13% and 21% following samples also had AFB2 contamination at 0.06 and 0.08 ppb, respectively ( 67 ). Khorasgani et al (2015) showed that the highest concentrations of AFB1 and total AFs in imported rice samples were 2.350 and 2.704 ng/g, respectively ( 68 ).…”
Section: Resultsmentioning
confidence: 99%
“…This issue has an impact on a sizable portion of the population, according to Rodriguez et al (2011). Malnutrition and developmental delays are major contributors to child mortality in developing nations, where they account for around half of all child fatalities (Karajibani et al, 2013). The rapid advancement of the nutrition transition in Sokoto has resulted in an increasing prevalence of obesity, which is a critical issue, especially in semi-urban and rural areas.…”
Section: Introductionmentioning
confidence: 99%